Diabetics and Oral Health: A Case-Control Study - Kabir , Mohammad Nazmul; Islam , Md Monoarul; Tarafder , Md Shahrin (Update Dental College Journal, 2021)
Background: Diabetes is a predominant health problem today and characterized by abnormally high blood sugar. According to World Health Organization (WHO) this clinical condition is increasing worldwide due to urbanization and physical inactivity uncontrolled diabetes develop ulceration, infection, tooth decay and decrease oral health status. Objectives: For the assessment of oral health condition and according to treatment required among the diabetic and non-diabetic patients is dental department of Cox’s Bazar Medical College Hospital, Cox’s Bazar. Method: This was a case-control type of study carried among 150 diabetics and 150 non-diabetics for 8 months period. Date was collected by direct interview of both diabetics and non-diabetics and clinical examination of oral cavity & also lab test. Results: Prevalence of Dental caries was higher in diabetics (58.6%) than non-diabetics (21.6%) and also prevalence of periodontal disease more in diabetics (93.2%) than non-diabetics (82.6%). Conclusion: Oral health is mirror image of general health. Dental caries and periodontal disease are more in diabetics than non-diabetics complex treatment required more in diabetics than non-diabetics. So, regular dental care is necessary for diabetic patients. Update Dent. Coll. j: 2021; 11(2): 32-34